Psychoanalytic and spiritual perspectives on terrorism - Cerfolio, Nina E. (Routledge, 2024)
"Nina E. Cerfolio masterfully explores the deeper spiritual and psychoanalytic understanding of the origins of human aggressive and destructive instincts which underlie mass shootings and terrorism. The author survived two terrorist attacks: developing breast cancer from being a first responder at 9/11, and being poisoned by an FSB agent while providing humanitarian aid in the Second Chechen War. Through a personal, scholarly investigation into her psyche, the author describes the spiritual awakening that was catalysed by these events and their traumatic impact, and examines how a world could create the firmament for the kinds of destructive aggression that are a daily occurrence. Featuring cutting-edge quantitative research and case material, which illustrates the prevalence of undiagnosed and untreated psychiatric illness among mass shooters and terrorists, this book encourages dialogue about the stigma of mental illness and challenges the perception of terrorists as monsters with no societal responsibility. Championing the forgotten collective humiliation of the marginalized-which in turn breeds terrorism-and documenting a new spiritual lens through which healing is possible, this book will be essential reading for mental health workers and anyone wishing to understand the traumatizing epoch in which we are living"--